2020
DOI: 10.1371/journal.pone.0237730
|View full text |Cite
|
Sign up to set email alerts
|

Tracking down carbon inputs underground from an arid zone Australian calcrete

Abstract: Freshwater ecosystems play a key role in shaping the global carbon cycle and maintaining the ecological balance that sustains biodiversity worldwide. Surficial water bodies are often interconnected with groundwater, forming a physical continuum, and their interaction has been reported as a crucial driver for organic matter (OM) inputs in groundwater systems. However, despite the growing concerns related to increasing anthropogenic pressure and effects of global change to groundwater environments, our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…Overall, our results from genetic analyses on stygofaunal gut microbiomes suggest that the inflow of OM at Sturt Meadows is exploited by microbes which are the potential direct (through biofilm grazing) and indirect (via POC assimilation) diet sources of primary consumers, amphipods and copepods. A previous investigation on carbon inputs in water indicated a shift in microbial taxonomic assemblages coupled with increased degradative pathways after rainfall (HR) 22 . In line with our work, Reiss et al 9 reported that rainfall inflows, coupled with increased inputs of organic matter mediate changes in microbial diversity, abundances and respiration rates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, our results from genetic analyses on stygofaunal gut microbiomes suggest that the inflow of OM at Sturt Meadows is exploited by microbes which are the potential direct (through biofilm grazing) and indirect (via POC assimilation) diet sources of primary consumers, amphipods and copepods. A previous investigation on carbon inputs in water indicated a shift in microbial taxonomic assemblages coupled with increased degradative pathways after rainfall (HR) 22 . In line with our work, Reiss et al 9 reported that rainfall inflows, coupled with increased inputs of organic matter mediate changes in microbial diversity, abundances and respiration rates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, further species-specific investigations are required to elucidate the mechanisms of these interactions and bring crucial comprehension of the dynamics sustaining groundwater biodiversity. (Table 1); (1b) as a result of the rainfall infiltration, phosphates dilute, carbonates are released (higher alkalinity) 23 and old POC gets to the water; (2) ammonia concentrations increase as a combined effect of animal waste leaking from the surface and microbial metabolisms 22,23 ); (3) microbial biofilms consume the newly incorporated old DOC (partially derived from POC (route 3b)) 22 ; (4) biofilms decompose POC; (5) harpacticoids browse on biofilm and cyclopoids filter particulate organic matter (route 6); (7a) amphipods graze on microbial mats (and filter POC (route 7b)) and fuel the carbon to the upper trophic levels; 8, beetles larvae and adults (route 9) (top predators) exert a higher trophic pressure on amphipods after rainfall 7 . Dashed lines lead to the proportions of the carbohydrate, lipid and amino acid microbial metabolisms (diameter of the bubbles proportional to the relative abundances in cyclopoids, harpacticoids and AM1; inner orange circles under HR (b) are illustrated for comparison with the significative lower relative abundances under LR (a)).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations